2017
DOI: 10.3390/molecules22111994
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shenxiong Glucose Injection on the Activities of Six CYP Isozymes and Metabolism of Warfarin in Rats Assessed Using Probe Cocktail and Pharmacokinetic Approaches

Abstract: Shenxiong glucose injection (SGI), a traditional Chinese medicine (TCM) preparation, has been widely used for the treatment of various cardiovascular and cerebrovascular diseases for many years. We assessed the potential influences of SGI on the activities of six CYP enzymes (CYP1A2, CYP2C11, CYP2C19, CYP2D4, CYP2E1, and CYP3A2) and on the pharmacokinetics of warfarin in rats. We compared plasma pharmacokinetics of six probe drugs (caffeine/CYP1A2, tolbutamide/CYP2C11, omeprazole/CYP2C19, metoprolol/CYP2D4, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
(35 reference statements)
2
9
0
Order By: Relevance
“…In this experiment, we found that the T max was delayed for parent and metabolite and the C max was decreased for metoprolol; the results were similar to the research of Sun et al [29] and Hsueha et al [32, 33]and the C max , T 1/2 , and AUC showed similar tendency in the group of herb-drug combination compared with drug administration alone. The changes of PK parameters for metoprolol might be influenced by the metabolic enzymes.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this experiment, we found that the T max was delayed for parent and metabolite and the C max was decreased for metoprolol; the results were similar to the research of Sun et al [29] and Hsueha et al [32, 33]and the C max , T 1/2 , and AUC showed similar tendency in the group of herb-drug combination compared with drug administration alone. The changes of PK parameters for metoprolol might be influenced by the metabolic enzymes.…”
Section: Resultssupporting
confidence: 90%
“…The rats were randomly divided into CYP probe groups and metoprolol tartrate group. According to the recent study [29–31], we formulated the dose and route of administration of probe substrates. The CYP probe group comprised of three subgroups: rats in group A were given 2.5 mL/kg solution of five probe drugs (5 mg/kg of omeprazole and phenacetin, 2 mg/kg of midazolam and dextromethorphan, and 4 mg/kg of tolbutamide) through tail vein; rats in group B were administered 500 mg/kg NXT by oral administration and then after 5 minutes, dosed with 2.5 mL/kg solution of five probe drugs through tail vein; rats in group C were given 500 mg/kg NXT by oral administration daily for 8 consecutive days and dosed through tail vein with a solution of five probe drugs on the eighth day.…”
Section: Methodsmentioning
confidence: 99%
“…substrates, special care should be taken during the selection of the substrate concentrations in assessing P450 activity, and reducing the dosage of the substrate is one of the most effective methods. Based on previous studies and our preliminary experiments, the concentrations of probe substrates are 0.4 mg/kg except for amodiaquine (1.2 mg/kg) (Han et al, 2014;Sun et al, 2017). Because of the interindividual variation of P450 activity, a sufficient number of subjects is required; therefore, eight rats were used in each group for pharmacokinetic studies to assess the activity of P450s in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…CYP450 enzymes serve as the major enzyme system that regulates TCM metabolism [36, 42, 43]. Among this superfamily, CYP3A4 is a major isozyme that is highly expressed in the liver and is known to metabolize many different drugs; CYP3A4 is regulated by pregnane X receptor (PXR) [44, 45].…”
Section: Discussionmentioning
confidence: 99%